2020
DOI: 10.3390/microorganisms8030384
|View full text |Cite
|
Sign up to set email alerts
|

Riboregulation in Nitrogen-Fixing Endosymbiotic Bacteria

Abstract: Small non-coding RNAs (sRNAs) are ubiquitous components of bacterial adaptive regulatory networks underlying stress responses and chronic intracellular infection of eukaryotic hosts. Thus, sRNA-mediated regulation of gene expression is expected to play a major role in the establishment of mutualistic root nodule endosymbiosis between nitrogen-fixing rhizobia and legume plants. However, knowledge about this level of genetic regulation in this group of plant-interacting bacteria is still rather scarce. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 140 publications
(255 reference statements)
0
12
0
Order By: Relevance
“…were found to be more abundant in rice roots expressing high levels of nitrogenase in the aerenchyma to indicate the location within the roots [ 68 ]. The process of nodulation and N 2 -fixation by endophytic rhizobia has been well studied and there are several excellent reviews available [ 69 , 70 , 71 ], and it is therefore not elaborated here ( Figure 1 ).…”
Section: Rhizosphere and Root Endophytesmentioning
confidence: 99%
“…were found to be more abundant in rice roots expressing high levels of nitrogenase in the aerenchyma to indicate the location within the roots [ 68 ]. The process of nodulation and N 2 -fixation by endophytic rhizobia has been well studied and there are several excellent reviews available [ 69 , 70 , 71 ], and it is therefore not elaborated here ( Figure 1 ).…”
Section: Rhizosphere and Root Endophytesmentioning
confidence: 99%
“…Recently, Hfq was shown to contribute to the distribution of sRNAs to the poles of E. coli cells experiencing envelope stress, suggesting a role for Hfq in spatiotemporal regulation of gene expression ( 18 ). Although previous studies have demonstrated a role for Hfq in the Ntr response in the N 2 -fixing symbiont Sinorhizobium meliloti ( 19 ), the role of Hfq-mediated riboregulation in the Ntr response of enterobacteria remains unknown. Hence, the initial aim of this study was to investigate the role of Hfq in regulating the flow of genetic information during the Ntr response in E. coli .…”
mentioning
confidence: 99%
“…Our knowledge about sRNAs is less advanced in other prokaryotes (Adams & Storz, 2020). sRNA-mediated gene expression control is known to be abundant in α-proteobacteria (Becker et al, 2014;Robledo et al, 2020). Examples are the regulation of photosynthesis genes by the sRNA PcrZ in Rhodobacter sphaeroides (Mank et al, 2012) or the sRNAs EcpR1 modulating cell cycle progression, and NfeR1 involved in osmoadaptation and symbiotic efficiency in the nitrogen-fixing plant symbiont Sinorhizobium meliloti (Robledo et al, 2015(Robledo et al, , 2017.…”
mentioning
confidence: 99%